Tolerância de cultivares de feijão (phaseolus vulgaris l.) aos herbicidas inibidores da enzima protoporfirinogênio oxidase - Brusamarello, Antonio Pedro (2019)
For bean crop there are few registered herbicides that exert crop selectivity and are efficient in controlling broadleaf weeds. This underscores the great importance of research investigating the tolerance of the bean to herbicides that do not yet have a record to the crop, as new alternatives for the control of weeds. Recent studies have confirmed the existence of variability of tolerance of bean cultivars to saflufenacil herbicide, inhibitor of the protoporphyrinogen oxidase (Protox) enzyme, when applied in the pre-emergence mode of the culture. The present work aimed to investigate the tolerance of beans to herbicides inhibitors of Protox enzyme. The experiments were performed to determine: (1) the differential tolerance of safluenacil herbicide in pre and post emergence modalities; (2) the existence of different tolerance levels among bean cultivars; (3) herbicide tolerance of different Protox inhibitor chemical groups; (4) the selectivity of different doses of saflufenacil and sulfentrazone in bean cultivars and the effect on weed control; and (5) tolerance mechanisms based on herbicide metabolism. The results allow us to infer that the bean tolerance levels to saflufenacil are much higher in the preemergence modality than the postemergence, in which very low doses of saflufenacil cause plant death. Among the cultivars tested, BRSMG Talismã and IAC Milênio presented, respectively, the highest and lowest tolerance to saflufenacil (20.5 g ha-1). The tolerance to the saflufenacil, sulfentrazone, flumioxazin and fomesafen herbicides applied in pre-emergence depends on the cultivar and dose used, and there is no cross tolerance pattern to Protox inhibitors in the cultivars. In field conditions, saflufenacil presented satisfactory control of weeds only at the dose of 52.5 g ha-1, which caused high phytotoxicity to the bean. Sulfentrazone (400 g ha-1) showed satisfactory level of weed control and selectivity for the cultivars BRSMG Talismã and IPR Tuiuiú, showing good potential to be used in pre-emergence on latosol type soil. In greenhouse trials, increased tolerance of the sensitive cultivar with mefenpyr-diethyl protector and the reduction of tolerance of the tolerant cultivar to the chlorpyrifos inhibitor, suggest that the metabolism is involved in the mechanism of tolerance to Protox inhibitors. It is concluded that the tolerance level manifested in pre-emergence is dependent on the cultivar and herbicide employed, suggesting the involvement of herbicide metabolism as one of the mechanisms of bean tolerance to Protox enzyme inhibitors.